Resource Management of General Beam Steering Bistatic SAR for Performance Optimization - Chen, Tianfu; Sun, Zhichao; Wu, Junjie; Yang, Jianyu; Liu, Lin (IEEE transactions on geoscience and remote sensing, 2023)
In the beam steering bistatic synthetic aperture radar (BS-BiSAR) system, both the transmitter and receiver beams can be steered in the azimuth direction, offering increased flexibility in mission planning to meet specific imaging requirements. Compared with the current SAR system, the system resources of BS-BiSAR have a high degree of freedom (DOF), including bistatic configuration, beam steering modes, and pulse repetition frequency (PRF), which are closely related to imaging performance. With appropriate beam steering strategy and observation geometry, better cooperation of beam footprints of the platforms can be achieved for enhanced imaging performance. This article aims to explore the resource management problem (RMP) for BS-BiSAR and optimize the comprehensive system performance, including imaging area, spatial resolution, signal ambiguity, and radiometric performance. The RMP is then formulated as a single-objective problem subject to multiple constraints. An improved particle swarm optimization (PSO) method combined with a sentry learning strategy is proposed to solve the optimization problem under strict constraints and high-dimensional solution space. Simulation experiments are conducted to validate the effectiveness of the proposed method for managing system resources and optimizing performance. The result of the resource management method can be applied to guide the system design and achieve the comprehensive performance optimization of BS-BiSAR.